Quranic recitation for depression & anxiety: present literature and future - Md Rosli, Ahmad Nabil (2018)
Spiritual therapy is not new in our community. There is a considerable evidence to support the use of spiritual practices such as yoga, meditation, and mindfulness in treating negative psychological symptoms or mental disorders. In accordance with this, researchers have been investigating the positive effect of Quranic recitation on the medical and psychiatric patients. This review aims to systematically explore the effect of Quranic recitation on depressive and anxiety symptoms. The strengths and limitations of these studies will be discussed.